2023
DOI: 10.1136/bmjopen-2023-079084
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety symptoms and associated factors among school students after 2 years of the COVID-19 pandemic: a cross-sectional study in Zhejiang Province, China

Hao Wang,
Yi Zhou,
Pinyuan Dai
et al.

Abstract: ObjectivesTo ascertain the prevalence and associated factors of anxiety symptoms among middle and high school students in Zhejiang after 2 years of the COVID-19 pandemic.DesignA school-based cross-sectional study.Setting30 counties/districts in Zhejiang Province, China.Participants27 019 students attending middle and high schools.Outcome measuresAnxiety symptoms were assessed using the Generalised Anxiety Disorder 7-item scale (GAD-7). A total score of 10 or more is considered indicative of anxiety symptoms.Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…A foreign meta-analysis showed that the prevalence of COVID-19 has a greater impact on college students, specifically in terms of anxiety, depression, and stress, especially for women as well as final-year students (Baranauskas et al, 2022). Domestic large-scale surveys in Guangdong and Hubei at the beginning of 2020 showed that the incidence of depression during the epidemic among college students was 21.2% and 37.92%, and the incidence of anxiety was 26.6% and 34.3%, respectively (Wang et al, 2023), and there were grade differences, with the detection rate of anxiety, depression, and sleep disorders being much higher than that of lower-grade students in the case of higher-grade graduates who faced such important nodes as graduation defences, interviews, and job searches, and the number of sports. The detection rate of anxiety, depression and sleep disorders was much higher than that of lower grade students, and the amount of physical activity was lower than that of lower grade students.…”
Section: Discussionmentioning
confidence: 99%
“…A foreign meta-analysis showed that the prevalence of COVID-19 has a greater impact on college students, specifically in terms of anxiety, depression, and stress, especially for women as well as final-year students (Baranauskas et al, 2022). Domestic large-scale surveys in Guangdong and Hubei at the beginning of 2020 showed that the incidence of depression during the epidemic among college students was 21.2% and 37.92%, and the incidence of anxiety was 26.6% and 34.3%, respectively (Wang et al, 2023), and there were grade differences, with the detection rate of anxiety, depression, and sleep disorders being much higher than that of lower-grade students in the case of higher-grade graduates who faced such important nodes as graduation defences, interviews, and job searches, and the number of sports. The detection rate of anxiety, depression and sleep disorders was much higher than that of lower grade students, and the amount of physical activity was lower than that of lower grade students.…”
Section: Discussionmentioning
confidence: 99%